Legal Aspects of The Use of Artificial Intelligence (AI) in Health Students: Bibliometrics Analysis - Fitriani Nur Damayanti; Sri Rahayu (Jurnal Kebidanan, 2025)
The opportunities perceived by healthcare students for AI include increased efficiency and reduced workload. The challenges perceived by healthcare students for AI include its impact on concerns about technology dependency.The purpose of this study is to determine the trend of the number of publications on the legal aspects of the use of artificial intelligence in health students, the number of citations, and the direction of future research topics. The research method applied in this study is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) which uses 26,881 scientific articles or proceedings sourced from the Dimensions database. Article review uses the VOSviewer application. The results of the study revealed that the number of publications on the topic of the legal aspects of the use of artificial intelligence (AI) in health students has an upward trend, the number of citations on the topic of the legal aspects of the use of artificial intelligence (AI) in health students has increased, network visualization on the topic of the legal aspects of the use of artificial intelligence (AI) in health students provides information to find novelty on topics that are not yet connected, there are 5 clusters reviewed from co-occurrence, overlay visualization on the topic of labor pain intervention provides a trend in the direction of future research topics, density visualization on topics that are still rare. The results of this study contribute to the development of a research roadmap on the legal aspects of the use of artificial intelligence (AI) in health students.